Potamophilus acuminatus (Fabricius, 1792): distribution update in North Africa confirmed by COI barcoding sequencing (Coleoptera, Elmidae) - Kodada, Ján; Bennas, Nard; Goffová, Katarína; Čiampor , Fedor Jr (Zootaxa, 2022)
Potamophilus acuminatus (Fabricius, 1792) is here recorded for the first time from Morocco and the recent distribution in Slovakia is updated. The North African distribution was hitherto based only on two larvae from Tunisia. DNA-barcoding confirmed the identification of specimens from Morocco after comparing ten sequences of P. acuminatus from Germany, France and Slovakia. The COI haplotype of the Moroccan samples was quite divergent (0.033–0.035 uncorrected p-distance) compared with European specimens. These high p-distances suggest the existence of a different intraspecific lineage. A brief morphological diagnosis of adults and larvae is given.